Efficacy and safety of Chinese classical prescriptions for dilated cardiomyopathy: a systematic review and Bayesian network meta-analysis - Shiyi Tao; Lintong Yu; Jun Li; Ji Wu; Xiao Xia; Yonghao Li; Deshuang Yang; Wenjie Zhang (Systematic Reviews)
Abstract Background Chinese classical prescriptions (CCPs) are commonly utilized in China as an adjuvant treatment for dilated cardiomyopathy (DCM). Nevertheless, there was insufficient systematic evidence data to show the advantages of CCPs plus current conventional therapy (CT) against DCM. This network meta-analysis (NMA) sought to evaluate and prioritize the six different CCP types’ respective efficacies for DCM. Methods A comprehensive search was conducted from the databases’ inception to November 30, 2024, to extract RCTs that addressed the use of CCPs in conjunction with CT for DCM. The databases included PubMed, Embase, Web of Science Core Collection, Cochrane Library, ProQuest, China National Knowledge Infrastructure (CNKI), China Science Periodical Database (CSPD), Chinese Citation Database (CCD), Chinese Biomedical Literature Database (CBM), and ClinicalTrials.gov. The Cochrane Risk of Bias assessment tool was used to evaluate the quality of the included RCTs. Surface under the cumulative ranking curve (SUCRA) probability values was employed to rank the relative efficacy. Bayesian network meta-analysis was applied to evaluate the efficacy of various CCPs. This review was registered with PROSPERO (CRD42024586365). Results Following the application of inclusion and exclusion criteria, 27 eligible RCTs involving 2019 patients were included. The evaluated outcomes included clinical effectiveness rate (CER), left ventricular ejection fraction (LVEF), left ventricular end-diastolic dimension (LVEDD), left ventricular end-systolic dimension (LVESD), brain natriuretic peptide (BNP), cardiac output (CO), hypersensitive C-reactive protein (hs-CRP), and six-min walk test (6MWT). According to the NMA, Zhigancao decoction (ZGCD), Zhenwu decoction (ZWD), Shenfu decoction (SFD), Shengmai powder (SMP), Yangxin decoction (YXD), and Buyang Huanwu decoction (BYHW) in addition to CT considerably enhanced DCM treatment outcomes when compared to CT alone. SMP + CT (MD = 12.75, 95%CI 8.28–17.22) showed the highest probability of being the best treatment on account of the enhancement of LVEF. SFD + CT was most likely to be the optimal intervention for LVEDD decrease (MD = -4.68, 95%CI -8.73 to -0.62). YXD + CT (MD = -4.47, 95%CI -4.47 to -4.47) had the highest likelihood of being the optimal therapy for reducing LVESD. ZGCD + CT seemed to be the most promising intervention on the improvement in hs-CRP (MD = -2.82, 95%CI -3.60 to -2.04) and 6MWT (MD = 141.00, 95%CI 136.57 to 145.43). However, the optimal CCP for improving BNP and CO could not be identified based on the present studies. No significant adverse events emerged in the included studies. Conclusion This NMA indicated that adding CCPs to current CT treatment had a favorable effect on DCM. In light of the clinical efficacy and other outcomes, SMP + CT, SFD + CT, YXD + CT, and ZGCD + CT demonstrated a preferred improvement in patients with DCM when combined. Furthermore, additional larger RCTs with longer follow-up periods and standardized outcome reporting are required to give more solid evidence to support our findings due to the small sample size of the current studies and the presence of risk of bias.